P.23 Relationship Between Aortic Stiffness, Aortic, and Carotid Impedance with Vascular Aging in Community-Based Healthy People - Chao-Feng Liao (Artery Research, 2020)
Background: Stiffening of the aorta has been associated with microvascular structural brain damage and cognitive dysfunction in cross-sectional and longitudinal studies, probably due to the reduced wave reflection at the interface between carotid and aorta and transmission of excessive flow pulsatility into the brain. The present study investigated whether age-related stiffening of the proximal aorta is disproportionately greater than the carotid arteries and whether the coupling of stiffness between proximal aorta and carotid arteries affects wave reflection at the interface. Methods: Comprehensive pulsatile hemodynamics evaluation using applanation tonometry, carotid ultrasonography and echocardiography was performed in 1236 apparently healthy community residents (age range 40 to 96 years, average 62.4 ± 10.5 years) who had no history of cardiovascular events and stroke. Aortic (Zc) and carotid (CCI) characteristic impedance were estimated in the time domain. Carotid pulsatility index (PI) was computed from the carotid flow and a carotid reflection coefficient was computed from bilateral carotid impedance and distal aortic impedance. Results: CFPWV (Standardized Beta = 0.56, p < 0.001), CCI (Beta = 0.46, p < 0.001) and carotid reflection coefficient (Beta = 0.26, p < 0.001) significantly increased with age. In contrast, PI (Beta = −0.06, p = 0.026) significantly decreased with age, and a U-shape association between Zc (Beta = 0.09, p = 0.002) and age was found. Carotid flow PI was significantly related to the aorta-carotid reflection coefficient negatively (r = −0.28, p < 0.001). Conclusions: In this healthy population, stiffening of the proximal aorta was not disproportionately greater than that of the carotid arteries. This might favorably maintain the wave reflection at the carotid-aorta interface so that carotid flow PI did not increase with age.